GERAKAN MASYARAKAT PETANI MERESPON PROGRAM KEMITRAAN PENGEMBANGAN PERKEBUNAN KELAPA SAWIT DI SINGKOYO KABUPATEN BANGGAI - , Nur Rosintah Triana Tahwali ([Yogyakarta] : Universitas Gadjah Mada, 2011)
This thesis analyzes the actions of the Singkoyo farmers struggle against the private sector that is supported by government policy. This research is important because the movement of farmers is an effort to uphold the interests and presence in the system that discriminated farmer on oil palm plantation management partnership with PT Kurnia Luwuk Sejati. In the future this research can be expected to contribute to social movements and involvement (participation), community resulting in changing patterns of development that have favored the interests of society. To track the process of Singkoyo farmers movement, researcher using the contentious politics theory that is able to explain comprehensively about the process and forms of strategic movement. This study explore how the process and the strategic dynamics of the movement, how organizers of the movement capable of mobilizing the masses, taking advantage of existing opportunities and the chance (opportunity structure) and framing thought generally to be involved in a movement that aims to change a condition that discriminate Singkoyo farmers society. The research method is an explorative qualitative method to explore in depth the process of movement to positioning the existence and their interests in oil palm plantation development program. The study was preceded by collecting materials related to the object of study such as collecting data through observation and in depth interviews. Then the data collected were analyzed and assembled into a study. By using the logic of contentious politics, this study concludes that the peasant society movement against Singkoyo economic power pursued with various forms of resistance to strengthen the bargaining position of communities within the plasma-core partnership pattern. Organizer for the movement to mobilize the masses to take advantage of regional autonomy, the issue of democratization, and framing the Regional Head election contemporary events giving rise to public confidence. The movement of farmers conducted by the conventional or formal struggle (demonstration, mediation, arbitration, consolidation and legalization) and the unconventional or rampage (occupation, sabotage and destructive acts). The process of struggle by encouraging response from the actors - government and private actors (firms) with various motives of interest. In this research theoretically also a portrait of the workings of the politics contention theoryâs key process in explaining the process of Singkoyo farming communitiesâmovement.